The role of IGF-1 as a major growth factor for myeloma cell lines and the prognostic relevance of the expression of its receptor - Sprynski, Anne Catherine; Hose, Dirk; Caillot, Laurent; Réme, Thierry; Shaughnessy, John D., Jr; Barlogie, Bart; Seckinger, Anja; Moreaux, Jérôme; Hundemer, Michael; Jourdan, Michel; Meißner, Tobias; Jauch, Anna; et al. (Blood, 2009)
A plethora of myeloma growth factors (MGFs) has been identified, but their relative importance and cooperation have not been determined. We investigated 5 MGFs (interleukin-6 [IL-6], insulin-like growth factor type 1 [IGF-1], hepatocyte growth factor [HGF], HB-epidermal growth factor [HB-EGF], and a proliferation-inducing ligand [APRIL]) in serum-free cultures of human myeloma cell lines (HMCLs). In CD45− HMCLs, an autocrine IGF-1 loop promoted autonomous survival whereas CD45+ HMCLs could not survive without addition of MGFs, mainly IGF-1 and IL-6. IGF-1 was the major one: its activity was abrogated by an IGF-1R inhibitor only, whereas IL-6, HGF, or HB-EGF activity was inhibited by both IGF-1R- and receptor-specific inhibition. APRIL activity was inhibited by its specific inhibitor only. Of the investigated MGFs and their receptors, only expressions of IGF-1R and IL-6R in multiple myeloma cells (MMCs) of patients delineate a group with adverse prognosis. This is mainly explained by a strong association of IGF-1R and IL-6R expression and t(4;14) translocation, but IGF-1R expression without t(4;14) can also have a poor prognosis. Thus, IGF-1-targeted therapy, eventually in combination with anti-IL-6 therapy, could be promising in a subset of patients with MMCs expressing IGF-1R.
Prepublished online as Blood first edition paper, February 24, 2009
Gesehen am 14.01.2022